Politik Pembangunan Hukum di Bidang Investasi Suatu Keniscayaan Konstitusi Ekonomi - Saut P. Panjaitan (The Constitutional Court of the Republic of Indonesia, 2010)
The idea of welfare state of Indonesia has to can realize the national of economy order. The 1945 Contitution of the Republic of Indonesia formulated the national economic aspect as an the constitution of economy or as a social contract of economy in order to realizing the constitutional market economy. This mean that all the policies and economic development must be taken care of constitutionally aspect, including the investment policies and regulations.